The Prognostic Value of High Sensitivity C-Reactive Protein in a Multi-Ethnic Population After More Than 10 Years of Follow-Up: The Multi-Ethnic Study of Atherosclerosis (MESA) - Cainzos-Achirica, Miguel (Int J Cardiol, 2018)
BACKGROUND: The prognostic value of hsCRP in contemporary multi-ethnic populations is unclear, particularly in statin users. The aim of this study was to characterize the prognostic utility of hsCRP for atherosclerotic CVD (ASCVD) risk prediction in a multi-ethnic population including non-users and users of statins followed for more than 13 years. Associations with heart failure (HF), atrial fibrillation (AF), venous thromboembolism (VTE), cancer, and all-cause death were also examined. METHODS AND RESULTS: We evaluated 6,757 participants from the Multi-Ethnic Study of Atherosclerosis (MESA; 1,002 using statins at baseline), median follow-up 13.2 years. Higher levels of hsCRP were associated with a higher risk of all study endpoints in the unadjusted Cox Proportional Hazards regression analyses, except AF. Among non-users of statins, hsCRP only remained associated with VTE after adjusting for ASCVD risk factors, and did not improve risk prediction. Among users of statins, hsCRP did not improve ASCVD risk prediction either, although it was strongly associated with incident HF (HR for hsCRP ≥2 vs <2 mg/L 3.99; 95% CI 2.02, 7.90) and all-cause death (HR 1.52; 95% CI 1.11, 2.08) in multivariable analyses, and hsCRP significantly improved prediction of HF (area under the curve [AUC] basic model 0.741, AUC basic+hsCRP 0.788). CONCLUSIONS: The utility of hsCRP for ASCVD prediction was modest. On the other hand, hsCRP was associated with incident VTE in statin non-users, and all-cause mortality and HF in statin users. In the latter, hsCRP improved the prediction of incident HF events. This finding should be replicated in larger cohorts.